2020
DOI: 10.14710/jgi.8.1.31-39
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan pola asuh dengan kejadian stunting balita dari keluarga miskin di Kota Palembang

Abstract: Background: Nutritional problems do not always occur in poor families, in fact many of under five years in poor families in good nutritional status which have normal height (not stunting) based on the parenting in the family. The positive parenting in poor families are feeding habit, parenting habit, hygiene habit and health services habit. Objectives: This research aim to observe the parenting of feeding habits, parenting habits, hygiene habits and health services habits on the incidence of toddler’s stunting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0
49

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 12 publications
5
15
0
49
Order By: Relevance
“…In the stunted group, mothers' parenting styles were dominated by mothers who raise fewer children, while in the nonstunted group, mothers with good parenting patterns dominate. This result was consistent with a study of poor families in Palembang, which explained that poorly developed groups mainly control poor eating habits, while normal groups dominate good eating habits 20 . Previous studies have shown that mothers of mothers with developmental delays did not have a fixed diet schedule for their children, except that they did not pay attention to the nutritional content of the food they give 12 .…”
Section: Resultssupporting
confidence: 92%
“…In the stunted group, mothers' parenting styles were dominated by mothers who raise fewer children, while in the nonstunted group, mothers with good parenting patterns dominate. This result was consistent with a study of poor families in Palembang, which explained that poorly developed groups mainly control poor eating habits, while normal groups dominate good eating habits 20 . Previous studies have shown that mothers of mothers with developmental delays did not have a fixed diet schedule for their children, except that they did not pay attention to the nutritional content of the food they give 12 .…”
Section: Resultssupporting
confidence: 92%
“…Our findings revealed a moderate correlation between feeding patterns and the incidence of stunting among children aged 0-59 months in Kalibuntu Village, Probolinggo Regency (Table .2). It is in line with a study by Bella, Fajar, and Misnaniarti (2020) in Palembang City among 100 mothers of toddlers from low-income families. The study found a significant association between feeding habits and the incidence of stunting in toddlers from low-income families (p=0.000).…”
Section: Kalibuntu Villagesupporting
confidence: 91%
“…10 Hasil penelitian ini juga sejalan dengan penelitian yang dilakukan pada balita stunting di Palembang, dimana pola asuh yang didalamnya termasuk pengasuhan ayah dan kebiasaan kebersihan (p<0,05), secara statistik berhubungan dengan kejadian stunting. 11 Pada perencanaan hidup berkeluarga dan pengasuhan tanggap responsif, kampung KB secara statistik tidak efektif dalam kedua intervensi tersebut (p>0,05). Akan tetapi jika dilihat skoringnya, sebagian besar ibu sudah paham perencanaan hidup berkeluarga (75%) dan dari persepsi ibu dan melakukan pengasuhan tanggap responsif pada anak-anaknya (55%).…”
Section: Pembahasanunclassified